Pengaruh Earning Per Share, Dividend Per Share dan Arus Kas Terhadap Harga Saham Pada Perusahaan LQ 45 - Heni; Hikmah (LPPM Universitas Putera Batam, 2022)
The survey was conducted among LQ45 companies listed on the Indonesian Stock Exchange (IDX). The survey covered 45 of his LQ companies listed on the Indonesian Stock Exchange (IDX) from 2016 to 2020. The extraction method is the rational extraction method, and the number of samples is 28 companies. The method used in this study is the logical sampling method. The results of this study show that the significance test for earnings per share and cash flow is 0.000 < 0.05, and the significance test for dividends per share is 0.073 > 0.05. It can be concluded that the dividend per share does not affect the share price of companies listed on the Indonesian Stock Exchange LQ45. Earnings per share, dividends per share, and cash flow all have significant effects on stock prices, with large values of 0.000 < 0.05. This study yields a coefficient of determination of 0.670. That means earnings per share, dividends per share and cash flow account for 67% of the company's LQ 45 stock price, with the remaining 33% accounting for another variable not explored here